PERKEMBANGAN KETERAMPILAN MOTORIK MELALUI KEGIATAN MENARI PADA ANAK USIA 5-6 TAHUN DI TK ISLAM HARAPAN INDAH PONTIANAK - Ira Nurmaya; Aloysius Mering; Muhammad Ali (Universitas Tanjungpura, 2020)
AbstractMotoric development is an essential factor in children's development. It develops along with the maturity of their nerves and muscles. Thus, every movement is the result of multiple interaction patterns of various parts of the body system that is controlled by the brain. Dancing is an engaging activity for children that can develop their gross motoric skills in a fun way. The poor gross motoric skills of children often occur because the activities provided by the teacher are less attractive; they do more fine motoric activities than gross motoric activities. This study aims to determine the development of gross motoric skills through dancing activities in children at Harapan Indah Islamic Kindergarten, Pontianak. This type of research is Classroom Action Research (CAR), involving 23 children. The data collection methods used were observation, used to collect data on children's gross motoric development, and interviews, conducted with class B6 teachers to find out the strategy applied to develop children's gross motor skills. Based on the results of daily measurements, the children's gross motoric development has increased progressively by a percentage of 88%. Therefore, the attempt to develop children's gross motoric skills at the Harapan Indah Pontianak Islamic Kindergarten group B2 is successful.Keywords: Classroom Action Research, Dance, Gross Motoric Development.